On the Modeling of Mobile Service Ecosystems - Kalevi Kilkki (International Telecommunications Society (ITS), 2020)
All ecosystem models are just rough approximations of reality. In the case of communications ecosys-tems, numerous actors interact with each other and create an incredibly complex process that tends to depress even the most diligent modeler. In recent decades, various methods have been used to solve this dilemma. This paper provides an account of some of the methods, including system dynamics, agent-based modeling, and value network analysis. In addition, an ecosystem model implemented in a spread-sheet format is discussed in more detail. An ecosystem model can be used to assess the relative im-portance of different factors, such as pricing and service quality on the profitability of service providers. Extensive ecosystem models are useful for enhancing our understanding of the complex processes occurring in ecosystems. In contrast, the models are hardly applicable for predicting how an ecosystem will evolve in the long term, because no ecosystem model can include all the influencing factors.
Keywords: 330; Modeling; ecosystems; mobile services; quality of service